(untitled) (International Journal of Nursing Education, 2021)
Purpose: The purpose of this research was to develop a professional competency evaluation model of nursing students. Method: It was conducted through a research and development process divided into 4 steps as follows.1) Studying and analyzing elements and indicators from documents, interviewing experts, focus group and surveying opinions. 2) Drafting a model by 10 experts applying the multi–attribute consensus reaching. 3) Implementing among nursing students, classmates, and teachers. 4) Evaluating by participants engaged in the implementation. The statistics for data analysis comprised mean, standard deviation, median, interquartile range, the Mann–Whitney U test and the Kruskal-Wallis Test. Findings: The results of the research were as follows. 1) The core competency of nursing students consisted of 7 elements and the functional competency included 4 elements. 2) The model had a structure that the evaluation objectives, expected outcomes, indicators, criteria, evaluators, method, duration, and feedback. 3) It had a discriminant validity and could distinguish different professional competencies of the nursing students.4) The model was at a high level for all its aspects; feasibility, appropriateness, accuracy, and usefulness. Conclusion: The model was to develop a professional competency of nursing students.